A Survey on Cognitive Biometrics: EEG based approach to user recognition - Bhagyashri D, Dangewar; Pujeri, RV (International Journal of Computer Sciences and Engineering, 2025)
Recent advances in signal processing have made possible the use of brain waves or EEG signals for user recognition and also for communication between human and computers. Electroencephalography (EEG) is sensitive to electrical field generated by the electric currents in the brain, and EEG recordings are acquired with portable and relatively inexpensive devices when compare to the other brain imaging techniques. EEG signals are representative signals containing the information about state of human brain. EEG signals are sometimes uses for clinical applications for medical diagnostics. The shape of the wave may contain useful information about the state of the brain. It has been known that different regions of the brain are activated according to the associated mental status, for example, emotional status, cognitive status, etc. Since the difference in activities of the brain causes the difference in characteristics of EEG, it has been attempted to investigate the brain activity through analyzing EEG.